Genitives in early English typology and evidence - Allen, Cynthia L., 1951- (Oxford : Oxford University Press, 2008)
This text considers how English possessives changed from '-es' to ''s' during the middle ages. The author draws together her own and others' research on syntactic and morphological change in order to assess and explain the roles of processing and pragmatics in the construction of grammars and grammatical change.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English language -- Possessives; English language -- Case; English language -- Syntax; English language -- Grammar, Historical; English language -- Early modern, 1500-1700 -- Possessives; English language -- Middle English, 1100-1500 -- Possessives